2021
DOI: 10.1111/hsc.13270
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID‐19 pandemic on community mental health: A psychometric and prevalence study in Turkey

Abstract: Background: COVID-19, which is characterised by life-threatening symptoms, difficulty in breathing, and pneumonia symptoms and requires global emergency intervention, may cause psychological problems such as phobia, fear and anxiety. This study aims to examine the psychometric properties of the Fear of COVID-19 Scale in Turkish people and to determine the level of fear of COVID-19 among Turkish people. Methods:The research was carried out between March and April 2020. A Personal Information Form and the FCV-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The results of this study are similar to the studies revealing that the fear of COVID-19 is higher in women [52][53][54]. Studies conducted on Turkish participants revealed that both in healthy normal population and athlete population, women had greater fear and anxiety for COVID-19 scales than men [38,43,[55][56][57][58]. The fact that women are more affected by psychological distress such as depression, anxiety, adjustment disorder, perceived stress, post-traumatic stress disorder and insomnia caused by COVID-19 can be explained by the fact that women are more psychologically vulnerable [59][60][61].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are similar to the studies revealing that the fear of COVID-19 is higher in women [52][53][54]. Studies conducted on Turkish participants revealed that both in healthy normal population and athlete population, women had greater fear and anxiety for COVID-19 scales than men [38,43,[55][56][57][58]. The fact that women are more affected by psychological distress such as depression, anxiety, adjustment disorder, perceived stress, post-traumatic stress disorder and insomnia caused by COVID-19 can be explained by the fact that women are more psychologically vulnerable [59][60][61].…”
Section: Discussionsupporting
confidence: 89%
“…Data collection tools COVID-19 Fear Scale (FCV-19S), has been developed and verified by Ahorsu et al [20]. It has been demonstrated in different studies that the FCV-19S scale is a reliable and valid measurement tool in determining the fear of catching COVID-19 [43][44][45]. And in this research, the COVID-19 Fear scale, which was adapted into Turkish by Satici et al [44] was used.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the research confirmed the existence of other important factors that influence the intention to use online shopping among older adults. Due to reduced social contact between individuals during the COVID-19 pandemic resulting from lockdown restrictions or the fear of COVID-19 ( Korukcu et al, 2021 ; Soofi et al, 2020 ), we examined the influence of herd behavior on the intention to use online shopping. Studies have examined the influence of herd behavior on technology adoption ( Handarkho and Harjoseputro, 2019 ; Y.…”
Section: Discussionmentioning
confidence: 99%
“…Social contacts between people have diminished during the COVID-19 pandemic either through lockdown restrictions or as a result of the fear of the virus ( Korukcu et al, 2021 ; Soofi et al, 2020 ). Therefore, in the COVID-19 situation, the subjective norm of potential users of new technologies ( Venkatesh et al, 2003 ) is affected by diminishing the element of social influence by not having the same amount of information available from their close social circles when deciding on whether to adopt a certain technology.…”
Section: Introductionmentioning
confidence: 99%
“…Also, recent studies have revealed certain gender-based differences in the fear experienced in relation to the COVID-19 pandemic. Females have significantly reported higher levels of fear of COVID-19 ( Humer et al, 2020 ; Korukcu et al, 2020 ; Liu et al, 2020 ; Qiu et al, 2020 ; Reznik et al, 2020 ; Trnka and Lorencova, 2020 ; Tzur Bitan et al, 2020 ; Koçak et al, 2021 ; Pak et al, 2021 ), depression, anxiety, and stress ( Mazza et al, 2020 ) than males.…”
Section: Introductionmentioning
confidence: 99%